Analysis of dengue serotype 4 in Sri Lanka during the 2012-2013 dengue epidemic - Uehara, Anna; Wilder-Smith, Annelies (The American journal of tropical medicine and hygiene, 2017)
Abstract: The four serotypes of dengue virus (DENV-1, -2, -3, and -4) have had a rapidly expanding geographic range and are now endemic in over 100 tropical and subtropical countries. Sri Lanka has experienced periodic dengue outbreaks since the 1960s, but since 1989 epidemics have become progressively larger and associated with more severe disease. The dominant virus in the 2012 epidemic was DENV-1, but DENV-4 infections were also commonly observed. DENV-4 transmission was first documented in Sri Lanka when it was isolated from a traveler in 1978, but has been comparatively uncommon since dengue surveillance began in the early 1980s. To better understand the molecular epidemiology of DENV-4 infections in Sri Lanka, we conducted whole-genome sequencing on dengue patient samples from two different geographic locations. Phylogenetic analysis indicates that all sequenced DENV-4 strains belong to genotype 1 and are most closely related to DENV-4 viruses previously found in Sri Lanka and those recently found to be circulating in India and Pakistan.
Gesehen am 24.09.2018